ENHANCING COMMUNITY HEALTH CENTER PERFORMANCE THROUGH PUBLIC SERVICE INNOVATION AND DIGITAL TRANSFORMATION STRATEGIES - Prianto, Arif; Rahayu, Agus; Gaffar, Vanessa; Adiwibowo, Lili (Universitas Dharma Wacana, 2024)
The performance of the Community Health Center (Puskesmas) has been in the spotlight of all parties concerned with its ability to adopt the right innovation strategy and implement appropriate digital transformation. This research aims to uncover (1) how public service innovation strategies impact digital transformation implementation; (2) their effect on Puskesmas performance; (3) the impact of digital transformation implementation on Puskesmas performance; and (4) the mediating role of digital transformation in this relationship within West Java, viewed from a strategic management perspective. This quantitative study was conducted across 285 from 1,098 Puskesmas in West Java Province, utilizing proportional random sampling. The sample consisted of Puskesmas distributed across cities and districts in the region, ensuring representation from each area. A questionnaire with a 5-point rating scale was the primary research instrument, validated for accuracy and reliability. Data analysis included descriptive categorization and inferential analysis using Partial Least Square (PLS) via SmartPLS. The study found that public service innovation strategies positively impacted digital transformation implementation and Puskesmas performance. Additionally, digital transformation implementation positively influenced Puskesmas performance, with digital transformation partially mediating the relationship between innovation strategies and performance.